Discriminant Analysis of E-Marketing Mix in Online Purchasing Decision and its Implication for Millenials Students Education - Padmalia, Metta (University of Merdeka Malang, 2019)
The study aims to analyze the variables of e-marketing mix (product, price, place, promotion, personalization, privacy, customer service, community, site, and sales promotion) that can differentiate consumer purchasing decisions from generation millenial and non-millenial. This study is expected to provide an understanding of digital consumer buying behavior related to the generation of millenials students. The study population are all the people who have made a purchase online, while samples are selected based on purposive random sampling as 200 respondents. The data analysis uses a discriminant analysis Â IBM SPSS Statistics program 22. The test results prove that the discriminant variable sites and communities are able to discriminate against cross-generational purchase decisions. https://doi.org/10.26905/jmdk.v7i2.3329